Humoral immunity for durable control of SARS-CoV-2 and its variants - Kotaki, Ryutaro; Moriyama, Saya; Takahashi, Yoshimasa (Inflammation and Regeneration, 2023)
The coronavirus disease 2019 (COVID-19) pandemic is ongoing because of the repeated emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants, highlighting the importance of developing vaccines for variants that may continue to emerge. In the present review, we discuss humoral immune responses against SARS-CoV-2 with a focus on the antibody breadth to the variants. Recent studies have revealed that the temporal maturation of humoral immunity improves the antibody potency and breadth to the variants after infection or vaccination. Repeated vaccination or infection further accelerates the expansion of the antibody breadth. Memory B cells play a central role in this phenomenon, as the reactivity of the B-cell antigen receptor (BCR) on memory B cells is a key determinant of the antibody potency and breadth recalled upon vaccination or infection. The evolution of memory B cells remarkably improves the reactivity of BCR to antigenically distinct Omicron variants, to which the host has never been exposed. Thus, the evolution of memory B cells toward the variants constitutes an immunological basis for the durable and broad control of SARS-CoV-2 variants.